Nitazoxanide in Acute Rotavirus Diarrhea: A Randomized Control Trial from a Developing Country - Samarendra Mahapatro; Nijwm Mahilary; Amit Kumar Satapathy; Rashmi Ranjan Das (Journal of Tropical Medicine)
Background. Acute diarrhea is one of the leading causes of childhood mortality, with rotavirus being an important pathogen. Nitazoxanide, an antiparasitic agent, has been shown to inhibit rotavirus. Objective. This double-blind, randomized trial was designed to study the role of nitazoxanide in acute rotavirus diarrhea. Methods. Of 174 children (12 months to 5 years) with acute diarrhea, 50 rotavirus positive cases were randomized. The intervention group received syrup nitazoxanide twice daily (100 mg in 12–47 months, 200 mg in ≥4 yr) for 3 days along with standard treatment of diarrhea. Duration of diarrhea was the primary outcome measure. Results. The median duration (hrs) of diarrhea (54 versus 80; 95% CI: –26 [–13.2 to –38.8]) and hospitalization (68 versus 90; 95% CI: –22 [–12.98 to –31.02]) was significantly shorter in the nitazoxanide group. No significant difference was seen in the median duration (hrs) of fever or vomiting or the proportion of children requiring parenteral rehydration. There was no report of any adverse events. Conclusions. Oral nitazoxanide is effective and safe in the management of acute rotavirus diarrhea in Indian children (CTRI REF/2016/10/012507).